A cowboy kind of love - Grant, Donna (Grant, Donna. Heart of Texas., 2021)
When the love of his life, who up and left him unexpectedly, returns, harboring a dangerous secret, Jace Wilder, unable to stay away, agrees to protect her but must decide if he is willing to trust her again.